Assessing pesticide residue occurrence and risks in the environment across Europe and Argentina - Alaoui, Abdallah (2024)
The widespread and extensive use of pesticides in European crop production to reduce losses from weeds, diseases, and insects may have serious consequences on the ecosystem and human health. This study aimed to identify 20 active substances of high health risk, based on their detection frequency within and across the environmental matrices (soil, crop, water, and sediment) and to identify their associated hazardous effects. A sampling campaign was conducted across 10 case study sites in Europe and 1 in Argentina and included conventional and organic farming systems. In 31% of cases, the detected substances were found at a higher concentration in the soil than in the corresponding crops, 93% of the compounds were fungicides, and the remainder were insecticides. 43% of the substances, 57% of which were insecticides, were detected only in soil. There was a clear relationship between soils and crops in terms of contamination, but not between water and sediment. Portuguese soil (wine grapes) had the highest number of substances (12) with average concentrations (AC) varying between 1 and 162 μg/kg, followed by French (11 substances in wine grapes) (1≤AC≤64 μg/kg) and Spanish soils (9 substances in vegetables) (3≤AC≤59 μg/kg). The crops corresponding to these soils contained a relatively high number of detected substances and several in high average concentrations (AC). The risk quotient was consistently higher for conventional farms than for organic farms. For the soils from conventional farms, 5 active substances (chlorpyrifos, glyphosate, boscalid, difenoconazole, lambda-cyhalothrin, and one metabolite: AMPA) were considered high risk. For water samples, 2 substances (dieldrin and terbuthylazine) found were high risk, and for sediment, there were 3 substances (metalaxyl-M, spiroxamine, and lambda-cyhalothrin). There were 6 substances detected in crops that are suspected to cause human health effects. Uncontaminated soil is a prerequisite for the adoption of sustainable alternatives to pesticides. Efforts are needed to elucidate the unknown effects of mixtures, including biocides and banned compounds in addition to the substances used in agriculture.